Studi Optimalisasi Rute Pengangkutan Sampah Stationary Container System Berbasis Sistem Informasi Geospasial (SIG) di Kecamatan Balikpapan Timur - Putri, Iqoh Andini; Rini, Intan Dwi Wahyu Setyo; Hayati, Rina Noor (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
Waste transportation in East Balikpapan District currently does not have an effective waste transportation route, this has resulted in not optimal waste transportation, which is indicated by the large amount of waste accumulated at the TPS. Based on these problems, East Balikpapan requires optimizing waste management, especially in waste transportation, to reduce the accumulation of waste in TPS, which can cause environmental pollution. The research procedure used is to optimize the Waste transportation route in the East Balikpapan District using a qualitative descriptive method. Through this method, this research can improve the waste transportation system at the research location by providing improvements that are modelled using Geographic Information Systems (GIS). Determination of the most effective transportation route will be adjusted to the condition of the road being traversed, the distance travelled and the speed of the vehicle in the waste transportation process as well as the time it takes for the SCS (stationary container system) system to transport waste. Based on the existing conditions, transporting two dump trucks takes 7 hours, and one dump truck takes 6 hours and 30 minutes, with a distance of 69 km, 68 km and 104 km. The distance and time for transporting waste under existing conditions can be optimized with alternative routes, optimization results for the three dump truck fleets, namely the distance of 68 km with a time of 6 hours, a distance of 46 km in 5 hours and a distance of 68 km with a time of 5 hours in 2 trips per day.